More Than Words: The Significances of K-Pop Idols’ Quotes in Relation to Their Songs - Rustiawati, Ariestadella Anida; Dewinta, Arlia Nata; Putri, Eva Nursetia; Yunia, Rizka Rahma; Nada, Amatullah Husnun (Faculty of Humanities, Diponegoro University, 2024)
This abstract discusses the significance of quotes from K-Pop idols and their relationship to the songs sung. This analysis aims to analyze the relationship between quotes from K-Pop idols and the messages contained in their songs to understand their impact on fans and K-Pop culture more broadly. To find out the coherence and types of quotes expressed, this research explains the strength of the quotes expressed by K-Pop idols and how the quotes are in harmony with K-Pop idol songs. This research uses a descriptive-qualitative research design. The data is in textual form, as seen from quotes written and transcribed from idols as well as song lyrics from idols. The data obtained are 5 song lyrics and 5 quotes taken from YouTube, Twitter, Lysn Bubble, concerts, and merchandise. Data analysis techniques by Spradley (2016) were used in this research. The four stages of analysis are domain, taxonomy, component, and search for cultural themes. The results of this analysis showed that quotes from RM used more personal pronouns and nouns, and the first quote that RM said was an emotional quote, which was categorized as a weak quote by DeFrank, Bivona, Chiaraluce, and Kahlbaugh (2019). The song's lyrics convey a message about self-confidence, strengthen the concept of personal agency, and emphasize the individual's ability to form emotions. The coherence of the two is mutually reinforcing the concept of loving themselves and believing that they can do anything according to their wishes and reality.